Whole-exome sequencing identifies rare genetic variations in German families with pulmonary sarcoidosis - Kishore, Amit; Petersen, Britt-Sabina; Nutsua, Marcel; Müller-Quernheim, Joachim; Franke, Andre; Fischer, Annegret; Schreiber, Stefan; Petrek, Martin (Human genetics, 2018)
Genome-wide and candidate gene studies for pulmonary sarcoidosis have highlighted several candidate variants among different populations. However, the genetic basis of functional rare variants in sarcoidosis still needs to be explored. To identify functional rare variants in sarcoidosis, we sequenced exomes of 22 sarcoidosis cases from six families. Variants were prioritized using linkage and high-penetrance approaches, and filtered to identify novel and rare variants. Functional networking and pathway analysis of identified variants was performed using gene ontology based gene-phenotype, gene-gene, and protein-protein interactions. The linkage (n = 1007-7640) and high-penetrance (n = 11,432) prioritized variants were filtered to select variants with (a) reported allele frequency < 5% in databases (1.2-3.4%) or (b) novel (0.7-2.3%). Further selection based on functional properties and validation revealed a panel of 40 functional rare variants (33 from linkage region, 6 highly penetrant and 1 shared by both approaches). Functional network analysis implicated these gene variants in immune responses, such as regulation of pro-inflammatory cytokines including production of IFN-γ and anti-inflammatory cytokine IL-10, leukocyte proliferation, bacterial defence, and vesicle-mediated transport. The KEGG pathway analysis indicated inflammatory bowel disease as most relevant. This study highlights the subsets of functional rare gene variants involved in pulmonary sarcoidosis, such as, regulations of calcium ions, G-protein-coupled receptor, and immune system including retinoic acid binding. The implicated mechanisms in etiopathogenesis of familial sarcoidosis thus include Wnt signalling, inflammation mediated by chemokine and cytokine signalling and cadherin signalling pathways.
Keywords: celogenomová asociační studie; Humans; Sarcoidosis, Pulmonary; Sequence Analysis, DNA; genové regulační sítě; genetické markery; Female; Phenotype; Gene Regulatory Networks; Genotype; lidé; genetická variace; sekvenční analýza DNA; Genetic Variation; Pedigree; rodokmen; ženské pohlaví; exom; Male; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; Genetic Markers; Exome; plicní sarkoidóza; Genome-Wide Association Study; genotyp; mužské pohlaví